2021
DOI: 10.1186/s12958-021-00749-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between steroid levels in follicular fluid and hormone synthesis related substances in its exosomes and embryo quality in patients with polycystic ovary syndrome

Abstract: Background Polycystic ovary syndrome (PCOS) is an endocrine and metabolic disorder with various manifestations and complex etiology. Follicular fluid (FF) serves as the complex microenvironment for follicular development. However, the correlation between the concentration of steroid in FF and the pathogenesis of PCOS is still unclear. Methods Twenty steroid levels in FF from ten patients with PCOS and ten women with male-factor infertility undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 41 publications
2
46
1
Order By: Relevance
“…It can deliver miRNAs, mRNAs and proteins involved in follicular development and oocyte maturation 24 , 25 . Previous studies have shown that miRNAs in exosomes derived from human follicular fluid play key roles in steroidogenesis and are closely associated with PCOS 26 , 27 . However, the mechanism of follicular fluid exosomal miRNAs in the pathological process of PCOS, especially in follicular development, is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It can deliver miRNAs, mRNAs and proteins involved in follicular development and oocyte maturation 24 , 25 . Previous studies have shown that miRNAs in exosomes derived from human follicular fluid play key roles in steroidogenesis and are closely associated with PCOS 26 , 27 . However, the mechanism of follicular fluid exosomal miRNAs in the pathological process of PCOS, especially in follicular development, is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The follicular uid exosomes were isolated by ultracentrifugation. Transmission electron microscopy, nanoparticle tracking analysis and western blot analysis are used to characterize exosomes according to our previous study [20]. Total RNA was extracted using TRIzol (Invitrogen), and RNA was then reversetranscribed using SuperScript First-Strand cDNA System (Takara) according to the manufacturer's instructions.…”
Section: Exosome Isolation Rna Isolation and Quantitative Rt-pcrmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is one of the prevailing gynecological and endocrine and metabolic disorders among women of reproductive age, representing one of the leading causes of anovulatory infertility. According to the criteria in practice, this disease affects 5% to 20% of women worldwide [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Until today, both the subsequent etiology and pathophysiology of PCOS remain unclear. To reduce the psychological and social pressures that come with this pathology, several studies were conducted to facilitate the diagnosis and treatments [ 1 , 76 ]. Patients with PCOS that undergo assisted reproductive techniques (ART) might present a poor to exaggerated response, low oocyte quality, ovarian hyperstimulation syndrome, as well as changes in the FF metabolites pattern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation